The R2-haplotype associated Asp2194Gly mutation in the light chain of human factor V results in lower expression levels of FV, but has no influence on the glycosylation of Asn2181 - Kolfschoten, Marijn van der Neut; Dirven, Richard J.; Vos, Hans L.; Bertina, Rogier M. (Thrombosis and Haemostasis, 2003)
The R2 haplotype of the FV gene spans from exon 8 through 25 and comprises several strongly linked polymorphisms in the FV gene, including some missense mutations. Carriership of the R2-FV allele has been associated with reduced plasma FV levels, increased FV1/FV2 ratios and mild APC resistance. Some studies have reported that carriership of the R2-FV allele is associated with an increased risk of venous thombosis. At this moment, the individual contribution to the R2-associated phenotypes of the different mutations linked to the R2 haplotype of FV is unclear. The main objective of our study was to obtain insight in the influence of the R2-related Asp2194Gly mutation on FV expression, FV structure and FV function using B-domainless rFV mutants. Replacing Asp at position 2194 by Gly resulted in a more than threefold reduction of rFV expression compared to rFV wild-type. Therefore, we propose that the R2-linked Asp2194Gly mutation is an important determinant of the association of the R2-FV allele with lower FV levels. Furthermore, the light chains from Asp2194Gly containing rFV mutants showed similar molecular weights as the light chains of the non-glycosylated rFVwt or the plasma FV2 isoform, indicating that glycosylation at Asn2181 is not stimulated by the presence of a glycine in position 2194. Finally, the apparent Kd for dissociation of the FXaVa complex (K1/2Xa) was not higher in rFV mutants with the Asp2194Gly mutation than for rFVwt, suggesting that also the affinity for negatively charged phospho-lipids is not affected by substitution of Asp into Gly at position at 2194.
Keywords: Factor V; HR2; recombinant; glycosylation; expression